INSP-11. Patient-centered monitoring and care of cognitive late effects in pediatric brain tumor survivors with and without Cerebellar Mutism Syndrome (CMS). (3rd June 2022) - Walsh, Karin; Sady, Maegan; Tiplady, Kaitlyn; van Scoyoc, Shawna; Weisman, Hannah; Hardy, Kristina
Abstract: Risks of cognitive late effects in children with brain tumors is well-established. However, group heterogeneity may limit generalizability and result in inadequate neurocognitive monitoring and care. Children with CMS have unique long-term cognitive risks and current knowledge may not adequately describe their experience or needs. The establishment and implementation of patient-centered, empirically-derived assessment of cognitive change following tumor diagnosis and treatment is a novel, precision-based approach to patient care. METHODS: 30 patients diagnosed with posterior fossa tumor who had at least 2 neuropsychological evaluations were included. Primary outcomes were processing speed (Wechsler PSI) and working memory (WMI). Secondary outcomes were verbal and nonverbal intellect. Reliable change indices (RCIs) were computed (Chelune et al., 1993). Using an 80% CI, 10% would be expected to decline, while 90% would stay stable or improve. RESULTS: Mean age in the full sample was 9.2 (3.32) years at T1 and 13.0 (4.11) years at T2, with an average of 2.7 (2.58) years between assessments. Males made up 56.7% of the sample. Five of the 30 (17%) were CMS+. The CMS+ patients were similar in age to CMS- patients, were predominantly male (80%), and mostly received photon radiation (60%). The full sample showed greater prevalence of declining verbal (21%), spatial (58%) and working memory (29%) functions than the expected (10%). The CMS+ group had higher rates of processing speed (50% v. 7%) and working memory (50% v. 27%) declines than the CMS- group. In contrast, the CMS- group appeared to show more prevalent declines in spatial reasoning than the CMS+ group (67% v. 33%). CONCLUSIONS: There appear to be unique domains impacted in the CMS+ group, which can convey specific long-term outcomes specific to this subgroup of patients. These results highlight the utility of individualized, empirically-driven analysis of change in cognitive functioning in this patient population.